Bacteriological quality test of air in the classrooms of Darur Abror Foundation School West Lombok Regency in 2022 - Nurhidayatullah Nurhidayatullah; Azwaruddin Azwaruddin; Liza Mimhalina (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
This study aims to determine the air quality in the classroom. The study showed the quality of air bacteria in the classrooms at the Darur Abror Foundation School (Sudak Gardens Hamlet, Terong Tawah Village, Labuapi District, West Nusa Tenggara, Indonesia) exceeded the predetermined limit on the number of germs in the room. According to Minister of Health Regulation No. 1405/MENKES/SKXI/2002, the germ number is 200-500 CFU/m3. The number of bacteria in the classroom is 2,699 CFU/m3. The most abundant characteristic according to the size of the bacteria is pinpoint. The shape of bacteria based on the number is circular, and the color of most bacteria is white.